Are left- and right-eye pupil sizes always equal? - Gonca Gokce Menekse Dalveren; Nergiz Ercil Cagiltay (Bern Open Publishing, 2019)
Eye movements provide very critical information about the cognitive load and behaviors of human beings. Earlier studies report that under normal conditions, the left- and right-eye pupil sizes are equal. For this reason, most studies undertaking eye-movement analysis are conducted by only considering the pupil size of a single eye or taking the average size of both eye pupils. This study attempts to offer a better understanding concerning whether there are any differences between the left- and right-eye pupil sizes of the right-handed surgical residents while performing surgical tasks in a computer-based simulation environment under different conditions (left hand, right hand and both hands). According to the results, in many cases, the right-eye pupil sizes of the participants were larger than their left-eye pupil sizes while performing the tasks under right-hand and both-hands conditions. However, no significant difference was found in relation to the tasks performed under left-hand condition in all scenarios. These results are very critical to shed further light on the cognitive load of the surgical residents by analyzing their left-eye and right-eye pupil sizes. Further research is required to investigate the effect of the difficulty level of each scenario, its appropriateness with the skill level of the participants, and handedness on the differences between the left- and right-eye pupil sizes.